2019
DOI: 10.1002/ceat.201800695
|View full text |Cite
|
Sign up to set email alerts
|

Purification of Nickel Sulfate by Batch Cooling Crystallization

Abstract: Cooling crystallization was successfully carried out in a batch cooling crystallizer from impure acidic solutions to recover nickel as nickel sulfate salt with three different cooling rates. The compositions of the solutions included impurities of sodium, magnesium, chloride, and sulfuric acid to mimic industrial nickel electrowinning process solutions. The results show that NiSO 4 Á6H 2 O mainly crystallized, and its solubility and purity decreased with the increase in the mass ratio of chloride to sulfate. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Nickel is an important component in a wide range of materials such as stainless steel, nickel-or copper-based alloys and catalysts, crystal UV-filters, and the cathode of ion batteries [1][2][3][4]. Among these, nickel containing electric vehicle batteries (EVBs) has seen a dramatic increase in production over the last decade as a result of the environmental targets set by, amongst others, the EU [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nickel is an important component in a wide range of materials such as stainless steel, nickel-or copper-based alloys and catalysts, crystal UV-filters, and the cathode of ion batteries [1][2][3][4]. Among these, nickel containing electric vehicle batteries (EVBs) has seen a dramatic increase in production over the last decade as a result of the environmental targets set by, amongst others, the EU [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Nickel can be recycled from various sources such as spent batteries, spent catalysts, or from process streams in the hydrometallurgical industry [4,[9][10][11]. In industrial hydrometallurgical production by electrowinning, nickel metal is produced from an electrolyte solution of nickel sulfate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Thus, several alternative approaches for nickel sulfate crystallization have been proposed, which include eutectic freeze crystallization, cooling crystallization, and antisolvent crystallization. 5,12 However, none of them have been applied in the industry due to their limited empirical data to ensure efficient production of NiSO 4 ·6H 2 O and their requirement for additional solvents/reactions. Despite the drawbacks of the conventional evaporative crystallization method, it has the advantage of a relatively high crystal growth rate, well-established procedures, and no requirement for additional solvents/reactions.…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously reported that nickel recovery from industrial sidestreams can be achieved by a number of hydrometallurgical-based routes such as chemical precipitation, 4,5 ion exchange, 6,7 membrane technology, 8 solvent extraction, 9,10 cooling crystallization 11,12 and electrowinning. 13,14 Of these, solvent extraction (SX) has become established as a commercially viable industrial-scale unit process that allows nickel capture.…”
Section: Introductionmentioning
confidence: 99%